Study of paclobutrazol application time and different varieties on the growth and production of cucumber plants (Cucumis sativus L.) - Amin Wahyudi Pane; Nini Rahmawati; Luthfi Aziz Mahmud Siregar (Talenta Publisher, 2026)
The decline in cucumber production is mainly due to inefficient cultivation therefore, plant growth regulators and superior varieties are needed to increase productivity. This study aimed to evaluate the effect of paclobutrazol application time and superior cucumber varieties on plant growth and yield. The research was conducted from August to October 2024 at Jalan Galang, Pagar Merbau III Village, Lubuk Pakam District, and at the Biotechnology Laboratory, Faculty of Agriculture, University of North Sumatra. The experiment used a randomized block design with two factors: paclobutrazol application time (7, 14, 21, and 28 DAT) and cucumber varieties (Monas F1, Komanda F1, and Zatavy F1), with three replications. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test at the 5% level. The observed variables included plant height, number of leaves, number of female flowers, male-to-female flower ratio, number of fruits, fruit length, fruit diameter, and fruit weight. The results showed that plants without paclobutrazol showed higher plant height and leaf number, whereas paclobutrazol application at 21 DAT improved yield components, including number of fruits, fruit length, fruit diameter, and fruit weight. Zatavy F1 showed the best growth performance, with an average plant height of 194.67 cm, 76.27 leaves, and fruit weight of 4,149.93 g per plant. Monas F1 produced earlier female flowers, shorter harvest age, and larger fruit size, averaging 14.60 fruits per plant, fruit length 34.53 cm, and fruit diameter 71.9 mm. No significant interaction was observed between the application time of paclobutrazol and variety.